Pygmalion in management - Livingston, J. Sterling (Boston, Mass. : Harvard Business Press, 2009)
"Numerous studies show that people will rise, or fall, to the level where their superiors believe them to be most capable. As a manager, it is up to you to have high expectations for your employees, and to communicate those expectations to them. In Pygmalion in Management, J. Sterling Livingston urges you to understand the power you have over your subordinates' success, and use it to benefit everyone involved."--BOOK JACKET.
"Originally published in Harvard business review in 1969"--T.p. verso.
Includes bibliographical references.
Keywords: Employee motivation; Labor productivity -- Management; Communication in management